Global stroke statistics - Thrift, A; Thayabaranathan, T; Howard, G; Howard, V; Rothwell, P; Feigin, V; Norrving, B; Donnan, G; Cadilhac, D (SAGE Publications, 2016)
Background Up to date data on incidence, mortality, and case-fatality for stroke are important for setting the agenda for prevention and healthcare. Aims and/or hypothesis We aim to update the most current incidence and mortality data on stroke available by country, and to expand the scope to case-fatality and explore how registry data might be complementary. Methods Data were compiled using two approaches: (1) an updated literature review building from our previous review and (2) direct acquisition and analysis of stroke events in the World Health Organization (WHO) mortality database for each country providing these data. To assess new and/or updated data on incidence, we searched multiple databases to identify new original papers and review articles that met ideal criteria for stroke incidence studies and were published between 15 May 2013 and 31 May 2016. For data on case-fatality, we searched between 1980 and 31 May 2016. We further screened reference lists and citation history of papers to identify other studies not obtained from these sources. Mortality codes for ICD-8, ICD-9, and ICD-10 were extracted. Using population denominators provided for each country, we calculated both the crude mortality from stroke and mortality adjusted to the WHO world population. We used only the most recent year reported to the WHO for which both population and mortality data were available. Results Fifty-one countries had data on stroke incidence, some with data over many time periods, and some with data in more than one region. Since our last review, there were new incidence studies from 12 countries, with four meeting pre-determined quality criteria. In these four studies, the incidence of stroke, adjusted to the WHO World standard population, ranged from 76 per 100,000 population per year in Australia (2009–10) up to 119 per 100,000 population per year in New Zealand (2011–12), with the latter being in those aged at least 15 years. Only in Martinique (2011–12) was the incidence of stroke greater in women than men. In countries either lacking or with old data on stroke incidence, eight had national clinical registries of hospital based data. Of the 128 countries reporting mortality data to the WHO, crude mortality was greatest in Kazhakstan (in 2003), Bulgaria, and Greece. Crude mortality and crude incidence of stroke were both positively correlated with the proportion of the population aged ? 65 years, but not with time. Data on case-fatality were available in 42 studies in 22 countries, with large variations between regions. Conclusions In this updated review, we describe the current data on stroke incidence, case-fatality and mortality in different countries, and highlight the growing trend for national clinical registries to provide estimates in lieu of community-based incidence studies.